High Incidence of Xenogenic Bone Marrow Engraftment in Pig‐to‐Baboon Intra‐Bone Bone Marrow Transplantation. Issue 4 (12th February 2015) - Tasaki, M.; Wamala, I.; Tena, A.; Villani, V.; Sekijima, M.; Pathiraja, V.; Wilkinson, R. A.; Pratts, S.; Cormack, T.; Clayman, E.; Arn, J. S.; Shimizu, A.; et al.
Abstract : Previous attempts of α‐1, 3‐galactocyltransferase knockout (GalTKO) pig bone marrow (BM) transplantation (Tx) into baboons have demonstrated a loss of macro‐chimerism within 24 h in most cases. In order to achieve improved engraftment with persistence of peripheral chimerism, we have developed a new strategy of intra‐bone BM (IBBM) Tx. Six baboons received GalTKO BM cells, with one‐half of the cells transplanted into the bilateral tibiae directly and the remaining cells injected intravenously (IBBM/BM‐Tx) with a conditioning immunosuppressive regimen. In order to assess immune responses induced by the combined IBBM/BM‐Tx, three recipients received donor SLA‐matched GalTKO kidneys in the peri‐operative period of IBBM/BM‐Tx (Group 1), and the others received kidneys 2 months after IBBM/BM‐Tx (Group 2). Peripheral macro‐chimerism was continuously detectable for up to 13 days (mean 7.7 days; range 3–13) post‐IBBM/BM‐Tx and in three animals, macro‐chimerism reappeared at days 10, 14 and 21. Pig CFUs, indicating porcine progenitor cell engraftment, were detected in the host BM in four of six recipients on days 14, 15, 19 and 28. In addition, anti‐pig unresponsiveness was observed by in vitro assays. GalTKO/pCMV‐kidneys survived for extended periods (47 and 60 days). This strategy may provide a potent adjunct for inducing xenogeneic tolerance through BM‐Tx. Abstract : The strategy of intra‐bone bone marrow transplantation in combination with conventional bone marrow transplantation results in a high incidence of bone marrow engraftment, a longer period of persistence of peripheral macrochimerism with donor‐specific unresponsiveness in vitro, and two‐month renal graft survival without T cell depletion in pig‐to‐baboon xenotransplantation.